2004
DOI: 10.1577/m03-065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acoustic Transmitters on Swimming Performance and Predator Avoidance of Juvenile Chinook Salmon

Abstract: The objective of this study was to determine whether juvenile Chinook salmon Oncorhynchus tshawytscha are negatively influenced by the intraperitoneal implantation of acoustic transmitters. We evaluated swimming performance and predator avoidance of juvenile salmonids implanted with acoustic transmitters that weighed up to 6.7% of the fish's body weight in air. Critical swimming speeds (U crit ) of tagged, sham-tagged (surgery but no tag), and control fish were measured in a respirometer to determine tag effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 25 publications
4
64
2
Order By: Relevance
“…However, our results showed even more damage to fish bearing external transmitters than fish bearing either gastric or surgically implanted transmitters. Previous studies as well as ours clearly show that juvenile Chinook salmon achieve neutral buoyancy by compensating for the excess mass of internally implanted transmitters by increasing the volume of gas in their swim bladder (Gallepp and Magnuson 1972;Anglea et al 2003) and…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…However, our results showed even more damage to fish bearing external transmitters than fish bearing either gastric or surgically implanted transmitters. Previous studies as well as ours clearly show that juvenile Chinook salmon achieve neutral buoyancy by compensating for the excess mass of internally implanted transmitters by increasing the volume of gas in their swim bladder (Gallepp and Magnuson 1972;Anglea et al 2003) and…”
Section: Discussionsupporting
confidence: 67%
“…This happens in part because a transmitter increases the mass of the fish. Previous studies have shown that fish compensate (achieve neutral buoyancy) for the additional mass of a transmitter by increasing the volume of gas in their swim bladder, thereby increasing their displacement (Gallepp and Magnuson 1972;Anglea et al 2003). As the fish pass through a turbine environment, they are initially exposed to increasing pressures as they pass through the turbine intake and approach the turbine distributor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has been conducted to evaluate tag effects among many species, transmitter types and sizes, and geographic areas. Specifically, laboratory research has evaluated the survival, growth, tag expulsion, swimming performance, stress levels, and predation of tagged versus untagged fish [4][5][6][7][8][9][10][11]. In these studies, untagged or sham-tagged fish (that is, fish handled in a manner identical to treatment fish, including incisions, but not implanted with a transmitter) typically serve as a comparison to tagged fish.…”
Section: Introductionmentioning
confidence: 99%
“…Some biologists have suggested that this tag burden not exceed 2% (Winter 1996). However, there have been numerous laboratory based studies that indicate that a tag burden higher than this may not influence swimming performance, growth, tag retention, or survival (Brown et al 1999(Brown et al , 2006(Brown et al , 2010Anglea et al 2004;Zale et al 2005). To this day, discussion continues about the 2% rule presented by Winter (1996).…”
Section: Transmitter Size Considerationsmentioning
confidence: 99%